Causes of social security contribution evasion in Zimbabwe - Rwafa, Livingstone T. (Midlands State University, 2017)
This study sought to investigate the causes of social security contribution evasion in Zimbabwe. In this study 228 social security contributors were used. The researcher used questionnaires as research instruments. The study showed that the main causes of social security contribution evasion in Zimbabwe are the negative macroeconomic fundamentals, planned behaviour and poor compliance culture. The study revealed that Economic deterrents do not influence the social security contribution evasion behaviour. This study recommends that to reduce social security contribution evasion, social security administrators should engage defaulting employers to come up with workable payment plans. Incentives for compliance such as penalties amnesty can be put in place to improve on compliance. The respondents rated social security contributions as very low and an increase in these can enforce a compliance culture. Finally it is also recommended that further research be undertaken in order to assess the causes of social security contribution evasion when the economic environment normalises as this research was done when Zimbabwe was facing difficult macro-economic conditions.